Exploration of Labour-Market Attitudes Towards Migrants Among University Students - Dajnoki, Krisztina; Kőmíves, Péter Miklós (International Journal of Engineering and Management Sciences, 2016)
The aim of this article is to present attitudes towards migration, migrants based on the results of a questionnaire filled out by university students. The definition of the migrants is followed by the results of the study. The results of the survey show that the students who consider themselves basically tolerant are rejecting migrants in action. The answers related to the educational level of the migrants have shown that basic qualification and professional knowledge can be assumed of the migrants, unless the respondents took the view that migrants have no measurable school education. The migrants’ attitudes towards work are generally wrong according to the respondents. Perhaps that is the reason why the people who filled out the survey would not work together with or employ migrants.